2013
DOI: 10.1163/15685373-12342099
|View full text |Cite
|
Sign up to set email alerts
|

Young Children’s Deference to a Consensus Varies by Culture and Judgment Setting

Abstract: Three-and 4-year-old Asian-American and Caucasian-American children were asked to judge which of a set of three lines was the longest, both independently and in the face of an inaccurate consensus among informants. Half of the children made their judgments privately; the other half made their judgments with the experimenter present. In the private setting, children were mostly resistant to the incorrect testimony from the consensus. By contrast, in the public setting, children were more deferential, less willi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(97 citation statements)
references
References 31 publications
8
85
2
2
Order By: Relevance
“…Corriveau and Harris (2010) showed that in such cases, the majority of 3-and 4-year-olds favored their own perceptual judgment. Only approximately 30% of children favored an alternative claim made by a threeperson consensus, similar to the percentage observed among adults in the classical Asch paradigm (see also Corriveau, Kim, Song, & Harris, 2013). Similarly, in a study involving estimations of the typical size of familiar animals, Haun and Tomasello (2011) found that 4-year-olds typically made their own judgment-mostly rejecting the judgment supplied by three peers.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Corriveau and Harris (2010) showed that in such cases, the majority of 3-and 4-year-olds favored their own perceptual judgment. Only approximately 30% of children favored an alternative claim made by a threeperson consensus, similar to the percentage observed among adults in the classical Asch paradigm (see also Corriveau, Kim, Song, & Harris, 2013). Similarly, in a study involving estimations of the typical size of familiar animals, Haun and Tomasello (2011) found that 4-year-olds typically made their own judgment-mostly rejecting the judgment supplied by three peers.…”
Section: Introductionsupporting
confidence: 57%
“…Indeed, Corriveau and Harris (2010) showed that, as compared with European American preschoolers, Asian American preschoolers were more deferential to informants' claims when facing a conflict between their own unequivocal perception of the situation and the claims made by a majority of three people (see also Corriveau, Kim, et al, 2013). This difference has also been found in children's imitation of a non-efficient model (DiYanni, Nasrini, Nini, Kurkul, & Corriveau, 2013).…”
Section: One Informantmentioning
confidence: 94%
“…It could be thus hypothesized that the consensus effect demonstrated in our study might be less strong with a successive presentation. Nonetheless, further research should be undertaken to disentangle the effect of these two kinds of consensus, distinguishing also, for instance, whether the consensus is unanimous (Corriveau & Harris, 2010;Corriveau, Kim, et al, 2013;Haun & Tomasello, 2011;Herrmann et al, 2013;Seston & Kelemen, 2014) or not (Chen et al, 2013;Corriveau et al, 2009;Turner et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…(Claidière & Whiten, 2012;DiYanni, Corriveau, Kurkul, Nasrini, & Nini, 2015;Haun, van Leeuwen, & Edelson, 2013;Nielsen, Moore, & Mohamedally, 2012). Arguably the most striking cases of conformity are situations in which preschoolers conform to others' judgments even when they themselves know better (Corriveau & Harris, 2010;Corriveau, Kim, Song, & Harris, 2013;Walker & Andrade, 1996). For example, in a version of Asch's famous conformity paradigm, children often adopted a peer majority's obviously erroneous judgment (Haun & Tomasello, 2011).…”
Section: Introductionmentioning
confidence: 99%